Internalisasi Karakter Melalui Pembelajaran Baca Tulis Al-Qur’an: Metode dan Dampaknya terhadap Anak - Najamudin Najamudin; Dede Dang Sudjana; Dwi Muliati; Ahmad Reza; Surahan Hidayat (PT. Student RIhlah Indonesia, 2026)
The purpose of this study is to analyze various BTA learning methods and examine their impact on children's character development, particularly in aspects of reinforcing monotheism, ethics, and religious moderation. This study uses a qualitative approach through library research methods. Data were obtained from scientific books and reputable journals published between 2020 and 2026, then analyzed using content analysis techniques to identify conceptual patterns, pedagogical relevance, and characterological implications of the BTA methods studied. The research results show that the talaqqi method combined with the approach of understanding meaning (tadabbur) has proven effective in integrating the values of monotheism into children’s consciousness more deeply. This integration contributes to enhanced mental resilience, the development of inner peace (thuma’ninah), as well as fostering tolerant, inclusive attitudes that are oriented toward the values of religious moderation. BTA learning based on the internalization of meaning also strengthens the connection between cognitive, affective, and spiritual aspects in the Islamic education process. The novelty of this research lies in the conceptual formulation that integrates Qur'an literacy with the reinforcement of mental health and the development of a moderate character as a unified pedagogical approach. The policy implications of these findings emphasize the need to reorient the BTA local content curriculum so that it not only focuses on technical reading fluency but also prioritizes the internalization of values, the development of good manners, as well as strengthening the psychosocial and spiritual dimensions of children within the framework of holistic Islamic education.